Konsep Relasionalitas Orang Manggarai Dalam Terminologi Hae Reba Menurut Filsafat Gabriel Marcel: The Concept of Relationalism of the Manggarai People in Hae Reba's Terminology According to Gabriel Marcel's Philosophy - Mathias Adon Adon (TOTOBUANG, 2022)
The focus of this research is on exploring the concept of the relationality of the Manggaraian people in the terminology of Hae Reba in the light of Gabriel Marcel's philosophy. Therefore, this study aims to make the concept of Hae Reba relationality a beautiful philosophical point for the rationality of the Indonesian nation. The method used in this research is interviews and literature studies which are carried out from a phenomenological perspective. This study found that the terminology of hae Reba contains the concepts of the relationality of the Manggaraian people in living together. Therefore, if the concept of relationality is dialogued with the concept of intersubjectivity of Gabriel Marcel, it will become a beautiful philosophical presentation of the rationality of the Indonesian nation. Keywords: Hae Reba, Relational, Gabriel Marcel, Manggarai Culture, and Local Wisdom.